Investigation of Adsorption Mechanism of Reagents (Surfactants) System and its Applicability in Iron Ore Flotation – An Overview - Pattanaik, Abhyarthana; Venugopal, R. (Colloid and interface science communications, 2018)
The low - grade ores invariably liberate in finer sizes and the fines contain good amount of iron values in it. Flotation is the most established solution, both technologically and economically compared to other alternatives for fines beneficiation. The selection of reagents and their administration system are of critical importance in view of varied mineralogy and size consist of feed material. In this paper, the reagents/surfactants used in direct and reverse flotation process of iron ore has been reviewed with the aim of identifying their usefulness and limitations coupled with adsorption mechanism and surface chemistry. This paper provides a glimpse of study on effect of other parameters like pH, chemistry and composition of pulp, zeta potential and electrostatic potential, temperature. An understanding of the mineral surface-specific adsorption mechanism and proper selection of the reagents system is mandated for successful and effective flotation performance. [Display omitted] •A classification of reagents for iron ore flotation and their adsorption mechanism have been summarized.•There is a strong relationship between reagents used and surface properties as well as mineralogy of ore for an efficient flotation.•The reagents to be chosen for floating the same ore depend upon the surface characteristics of minerals we want to float i.e. (Direct and Reverse flotation) and a better understanding of interfaces of solid, liquid and air phase is essential.•No universal reagent regime is there for any natural ore. Development of regent regimes and specific operating conditions (electro-chemistry and pulp chemistry) are mandated for an ore/material under investigation.